Design de mobiliário eco-sustentável em madeira : uma proposta Eco-Eficiente para Produtoras de Mobiliário - Viana, Inês Marques Duarte (2019)
The title of the investigation 'Design of Eco-Sustainable Furniture in Wood: An Eco-Efficient Proposal for Furniture Producers' arises from a greater need to practice sustainability along the processes which involve the use of wood on the production of furniture. Presently, it is considered that, planet Earth is at the limit of climate change, manifesting itself as a concerning global warming. The excessive exploitation and carelessness of human activities have affected the conditions that make the planet what it is, causing problems in the ecosystems’ life cycle. For this reason, it is crucial to rebalance these natural cycles and the Earth’s temperature, by raising the issue of sustainability. It is important that society is informed and conscious about the environmental problems and that they apply ecofriendly methods in order to begin to change this. The ecological condition must be improved, especially within the Design sector and productive enterprises, as they are closer to being able to change the mentality of society and persuade it to choose better options. It is also important that governmental entities are aware of this and contribute with tax incentives to the designers and producers, so that the final product is more affordable. Consequently, efficient and sustainable methods, for creating new household products are investigated and analyzed. Addressing different materials, finishes, joining systems and Sustainable Design processes, such as the product Life Cycle Analysis. In result, an Eco-Sustainable and Eco-Efficient methodological proposal is obtained, in order to present it to wood furniture producers. Before this proposal, three furniture producers were selected and analyzed in order to use them as examples and approach them with improvements. With the proposed methodology, furniture producers will be able to improve their products and production processes, in ecological quality, contributing to the sustainability of the planet. Thus, enabling future generations to live with the same quality of life